Postorotracheal intubation dysphagia in patients with COVID-19: a retrospective study - Saconato, Mariana; Maselli-Schoueri, Jean Henri; Malaque, Ceila Maria Sant’Ana; Marcusso, Rosa Maria; Oliveira, Augusto César Penalva de; Batista, Lucio Antonio Nascimento; Ultramari, Graziela; Lindoso, José Angelo Lauletta; Gonçalves, Maria Inês Rebelo; Sztajnbok, Jaques (São Paulo Medical Journal, 2025)
BACKGROUND: The cause of oropharyngeal dysphagia in patients with coronavirus disease (COVID-19) can be multifactorial and may underly limitations in swallowing rehabilitation. OBJECTIVE: Analyze the factors related to dysphagia in patients with COVID-19 immediately after orotracheal extubation and the factors that influence swallowing rehabilitation. DESIGN AND SETTING: A retrospective study. METHODS: The presence of dysphagia was evaluated using the American Speech-Language Hearing Association National Outcome Measurement System (ASHA NOMS) scale and variables that influenced swallowing rehabilitation in 140 adult patients who required invasive mechanical ventilation for >48 h. RESULTS: In total, 46.43% of the patients scored 1 or 2 on the ASHA NOMS (severe dysphagia) and 39.29% scored 4 (single consistency delivered orally) or 5 (exclusive oral diet with adaptations). Both the length of mechanical ventilation and the presence of neurological disorders were associated with lower ASHA NOMS scores (odds ratio [OR]: 0.80, 95% confidence interval [CI]: 0.74–0.87 P < 0.05; and OR: 0.13, 95% CI: 0.61–0.29; P < 0.05, respectively). Age and the presence of tracheostomy were negatively associated with speech rehabilitation (OR: 0.92; 95% CI: 0.87–−0.96; OR: 0.24; 95% CI: 0.80–−0.75), and acute post-COVID-19 kidney injury requiring dialysis and lower scores on the ASHA NOMS were associated with longer time for speech therapy outcomes (β: 1.62, 95% CI, 0.70–3.17, P < 0.001; β: −1.24, 95% CI: −1.55–−0.92; P < 0.001). CONCLUSION: Prolonged orotracheal intubation and post-COVID-19 neurological alterations increase the probability of dysphagia immediately after extubation. Increased age and tracheostomy limited rehabilitation.